Anchor capacity of split sets according to their bond length - Giraldo Paredez, Emiliano Mauro (2018)
The support in underground excavations is essential to preserve the life and health of the workers, damage to the equipment and to have proper progress of the excavation. The most common Rock support sets are the rock bolts, temporary or definitive. Among temporary rock bolts, there are the Split sets, widespread around the world due to their ease of installation and cheaper. Split Sets, have the appearance of a tube with a 15 mm slot in its entire length, manufacturers and suppliers recommended 38 mm diameter of drill holes and depths according to their length. In this research, the ground and holes were simulated with a special table and steel tubes. Split Sets, were conditioned to make anchors of 1, 2, 3, and 4 feet of bond length. Prepared the simulator tubes and Split Sets were installed, after which, were performed the pull test of the 3 samples for each bond length to determine their anchor capacity. Peak loads for each length researched were recorded in formats designed for this purpose. Compiling the recorded values and adjusting them according to certification of pressure gauge calibration carried out in UNI, obtained the anchor capacity for each of length tested. Results that have been captured in a table and graph, where is inferred that the anchor capacity of the Split Sets is affected by its bond length, and that do not have a relationship. Maximum bond length of anchorage tends to 4 feet, i.e., it is unnecessary to use greater lengths.